Aporte de la nueva museología española al Museo de los Niños de Costa Rica - Rodríguez Sánchez, Keilyn (2005)
El artículo que se ofrece consiste en una comparación etnográfica sobre propuestas educativas no formales, entre el Museo de los Niños de Costa Rica y seis museos o centros de ciencia españoles ubicados en lo que se conoce como la nueva museología. Se detallan los aspectos de la nueva museología española que pueden enriquecer la práctica del museo costarricense. The following article consists in an ethnographic comparison about non-formal educational proposals. This comparison is carried out between Museo de los Niños and other six museums or Science Centers located in Spain which are known as New Museology. Certain aspects in which the New Spanish Museology enriches the practice in Costa Rican museum are detailed.